Long COVID outcomes following omicron wave in non-hospital population - Ruiyin, Wang; Qi, Jia; Tingting, Wang; Yuqin, Yan; Yan, Jia; Kun, Peng (Frontiers in Public Health, 2024)
The understanding of LC among China's non-hospitalized population continues to be insufficient.. The study aimed to assess the prolonged effects within this population and to pinpoint the related risk factors. This research constitutes a prospective cohort study focusing on non-hospitalized individuals, aged between 18 and 59, who have been positively diagnosed with COVID-19. A logistic regression model, adjusted for multiple variables, was employed to scrutinize the correlation between demographic elements, lifestyle attributes, and health-related risk factors in relation to conditions and symptoms post COVID-19 infection. A total of 706 individuals participated in the 3-month follow-up, with 620 continuing on to the 6-month follow-up. The median age was 35(28,43) years, and 597(85%) are female. Upon follow-up,, Compared with patients without LC，patients with LC have a higher proportion of females (420 (87%) vs. 177(79%); p=0.010), were older (35 (29,44) years vs. 33 (27,41) years; p=0.010) and have more comorbidities. Out of all participants, 483 (68.4%) reported experiencing at least one symptom at the 3-month mark, while 49.7% reported symptoms persisting at the 6-month mark. At the 3-month follow-up, the most prevalent persistent symptoms were cough (46%), fatigue (38%), and shortness of breath (34%). Fatigue (25%), shortness of breath (22%), and sleep disorders (16%) were the most commonly reported symptoms in 6 month. Anxiety and depression were consistently reported as prevalent symptoms throughout the follow-up period. most patient symptoms fade over time, with the quickest decreases observed in cough (from 46% to 9%), expectoration (from 26% to 6.3%), smell disorder (from 16% to 3.9%), and taste disorder (from 18% to 3.5%). Male and those possessing advanced educational qualifications exhibit a decreased susceptibility to persistent cough. Conversely, older age and comorbidities were identified as risk factors for persistent fatigue and shortness of breath. In the after of COVID-19, it has been observed that the majority of patient symptoms tend to decrease over time. The primary residual symptoms noticed after a six-month follow-up were fatigue, dyspnea, and sleep disturbances. However, it's noteworthy that the risk factors associated with these symptoms exhibit subtle variations. Furthermore, depression and anxiety are frequently reported among COVID-19 survivors.